Cause for event: not-for-profit marketing through participant sports events - Taylor, Ruth; Shanka, Tekle (Westburn Publishers Ltd, 2008)
The purpose of this paper was to investigate the motivations, satisfaction and intention of participants attending a sports event organised by a not-for-profit organisation as a major avenue of cause promotion and source of revenue generation. A questionnaire was distributed via three avenues for participants to complete, resulting in a response of N = 218. The summary descriptive statistics found that overall, there was an evenly distributed age range of respondents, 55% being male. Two thirds of the respondents had participated in the event previously, with most taking part in the event with a partner or friends. Factor analysis found that four components of achievement, involvement, status and socialisation contributed to participants' motivations. The involvement component exhibited significance to overall satisfaction of the event, with overall satisfaction significantly relating to future event participation intention. These findings have significance for not-for-profit marketing strategies when segmenting those attending not-for-profit revenue generating events.